Heart Rate Complexity in US Army Forward Surgical Teams During Pre Deployment Training. Issue 5 (9th December 2019) - Mulder, Michelle B; Sussman, Matthew S; Eidelson, Sarah A; Gross, Kirby R; Buzzelli, Mark D; Batchinsky, Andriy I; Schulman, Carl I; Namias, Nicholas; Proctor, Kenneth G
Abstract: Introduction: For trauma triage, the US Army has developed a portable heart rate complexity (HRC) monitor, which estimates cardiac autonomic input and the activity of the hypothalamic-pituitary-adrenal (HPA) axis. We hypothesize that autonomic/HPA stress associated with predeployment training in U.S. Army Forward Surgical Teams will cause changes in HRC. Materials and Methods: A prospective observational study was conducted in 80 soldiers and 10 civilians at the U.S. Army Trauma Training Detachment. Heart rate (HR, b/min), cardiac output (CO, L/min), HR variability (HRV, ms), and HRC (Sample Entropy, unitless), were measured using a portable non-invasive hemodynamic monitor during postural changes, a mass casualty (MASCAL) situational training exercise (STX) using live tissue, a mock trauma (MT) STX using moulaged humans, and/or physical exercise. Results: Baseline HR, CO, HRV, and HRC averaged 72 ± 11b/min, 5.6 ± 1.2 L/min, 48 ± 24 ms, and 1.9 ± 0.5 (unitless), respectively. Supine to sitting to standing caused minimal changes. Before the MASCAL or MT, HR and CO both increased to ~125% baseline, whereas HRV and HRC both decreased to ~75% baseline. Those values all changed an additional ~5% during the MASCAL, but an additional 10 to 30% during the MT. With physical exercise, HR and CO increased to >200% baseline, while HRV and HRC both decreased to 40 to 60% baseline; these changes were comparable to those caused by the MT. All the changes were P  < 0.05. Conclusions: Various forms of HPA stress during Forward Surgical Team STXs can be objectively quantitated continuously in real time with a portable non-invasive monitor. Differences from resting baseline indicate stress anticipating an impending STX whereas differences between average and peak responses indicate the relative stress between STXs. Monitoring HRC could prove useful to field commanders to rapidly and objectively assess the readiness status of troops during STXs or repeated operational missions. In the future, health care systems and regulatory bodies will likely be held accountable for stress in their trainees and/or obliged to develop wellness options and standardize efforts to ameliorate burnout, so HRC metrics might have a role, as well.